Anticipatory and Compensatory Postural Adjustments in Response to Dynamic Platform Perturbation during a Forward Step. Issue 1 (2nd January 2023) - Wang, Yun; Watanabe, Kazuhiko; Asaka, Tadayoshi
Abstract: We investigated the generation of anticipatory (APAs) and compensatory postural adjustments (CPAs) in preparation for a step during support surface perturbation. Changes in anticipatory muscle activation in the trunk segment were predominantly in the co-contraction indices from −600 t 0 −400 ms to foot-off. Reciprocal indices of the shank muscles were pronounced in the APA intervals. During the CPA intervals, larger reciprocal muscle activities were detected compared to the APA intervals. The results showed subjects co-varied the reciprocal and co-contraction activations in postural muscles to counteract the perturbation and generate mechanical effects sufficient for stepping during the APA and CPA intervals. This study enhances our understanding of the interaction between the APAs and CPAs in balance maintenance.